The influence of differential leadership on employees’ deviant innovation behavior: An outsider subordinate perspective - Wu, Mengyun; Zhu, Yuqing; He, Qi; Zhang, Luan; Lu, Jie (Frontiers in Psychology, 2022)
Given the complex business environment worldwide and rapid development of information technologies, employees’ deviant innovation behavior has attracted increasing attention. However, few scholars have explored the internal mechanism of the influence of differential leadership on the deviant innovation behavior of outsider subordinates from a positive perspective. Based on relative deprivation theory and attribution theory, we construct a theoretical model to study the influence of differential leadership in family businesses on the deviant innovation behavior of outsider subordinates, and hypothesis testing is conducted based on 243 questionnaire responses. The result shows that: differential leadership has a positive impact on the deviant innovation behavior of outsider subordinates; relative deprivation plays a mediating role; and internal control personality enhances the moderation effect between relative deprivation and outsider subordinates’ deviant innovation behavior. This study provides a reference point for the promotion of the innovation performance both of employees and organizations.